Congenital insensitivity to pain associated with PRDM12 mutation: Two case reports and a literature review - Yu, Hanrui; Wu, Jie; Cong, Jinju; Chen, Mingxiong; Huang, Yifei; Yu, Jifeng; Wang, Liqiang (Frontiers in Genetics, 2023)
Background: PRDM12 is a newly discovered gene responsible for congenital insensitivity to pain (CIP). Its clinical manifestations are various and not widely known. Methods： The clinical data of 2 infants diagnosed with CIP associated with PRDM12 mutation were collected. A literature review was performed and clinic characteristics of 20 cases diagnosed with mutation of PRDM12 were summarized and analyzed. Results：Two patients had pain insensitivity, tongue and lip defect, and corneal ulcer. The genomic analysis results showed that variants of PRDM12 were detected in the two families. The case 1 patient carried heterozygous variations of c.682+1G >A and c.502C >T (p.R168C), which were inherited from her father and mother, respectively. Through a literature review together with our cases, we enrolled 22 patients diagnosed with CIP. There were 16 males (72.7%) and 6 females (27.3%). The age of onset ranged from 6 months to 57 years. The prevalence of clinic manifestation were 14 cases with of insensitivity to pain (63.6%), 19 cases with self-mutilation behaviors (86.4%), 11 cases with tongue and lip defect (50%), 5 cases with mid-facial lesion (22.7%), 6 cases with distal phalanx injury (27.3%), 11 cases of recurrent infection (50%), 3 cases (13.6%) with anhidrosis, and 5 cases (22.7%) with global developmental delay. The prevalence of ocular symptoms were 11 cases (50%) with reduced tear secretion, 6 cases (27.3%) with decreased corneal sensitivity, 7 cases (31.8%) with disappeared corneal reflexes, 5.5 cases (25%, 0.5 indicated a single eye) with corneal opacity, 5 cases (22.7%) with corneal ulceration, and 1 case (4.5%,) with corneal scar. Conclusion： The syndrome caused by PRDM12 mutation is a clinically distinct and diagnosable disease, which requires joint multidisciplinary management to control the development of the disease in order to minimize the occurrence of complications.